Same but different: Socially foraging ants backtrack like individually foraging ants but use different mechanisms. (October 2019) - Freas, Cody A.; Congdon, Jenna V.; Plowes, Nicola J.R.; Spetch, Marcia L.
Graphical abstract: Highlights: Backtracking inconsistent with established criteria in solitary foraging species. Backtracking mediated by the foraging column rather than panorama cues. Backtracking direction is dictated by the sun's position. Veromessor pergandei do not retain panorama information around nest. Abstract: Diverse species may adopt behaviourally identical solutions to similar environmental challenges. However, the underlying mechanisms dictating these responses may be quite different and are often associated with the specific ecology or habitat of these species. Foraging desert ants use multiple strategies in order to successfully navigate. In individually foraging ants, these strategies are largely visually-based; this includes path integration and learned panorama cues, with systematic search and backtracking acting as backup mechanisms. Backtracking is believed to be controlled, at least in solitary foraging species, by three criteria: 1) foragers must have recent exposure to the nest panorama, 2) the path integrator must be near zero, and 3) the ant must be displaced to an unfamiliar location. Instead of searching for the nest, under these conditions, foragers head in the opposite compass direction of the one in which they were recently travelling. Here, we explore backtracking in the socially foraging desert harvester ant ( Veromessor pergandei), which exhibits a foraging ecology consisting of a combination of social and individual cues in a column and fan structure. We find that backtracking in V. pergandei, similar to solitary foraging species, is dependent on celestial cues, and in particular on the sun's position. However, unlike solitary foraging species, backtracking in V. pergandei is not mediated by the same criteria. Instead the expression of this behaviour is dependent on the presence of the social cues of the column and the proportion of the column that foragers have completed prior to displacement.